DIALOG Project: Materials for Teaching Russian to Portuguese Speaking Students in an Academic Context. (2nd January 2022) - Prokopyshyn, Ana; Baldé, Nailia; Dutta, Jayanti; Hristovsky, Gueorgui
ABSTRACT : In this paper information is presented about a recent didactic project launched by the Faculty of Arts at the University of Lisbon, developed as a resource for teaching Russian. The authors are the lecturers of Russian Language and Culture at the Centre for Slavic Studies – a unit of the above-mentioned Faculty.